2014
DOI: 10.3389/fnagi.2014.00314
|View full text |Cite
|
Sign up to set email alerts
|

Slowing of EEG Background Activity in Parkinson’s and Alzheimer’s Disease with Early Cognitive Dysfunction

Abstract: Background: Slowing of the electroencephalogram (EEG) is frequent in Parkinson’s (PD) and Alzheimer’s disease (AD) and correlates with cognitive decline. As overlap pathology plays a role in the pathogenesis of dementia, it is likely that demented patients in PD show similar physiological alterations as in AD.Objective: To analyze distinctive quantitative EEG characteristics in early cognitive dysfunction in PD and AD.Methods: Forty patients (20 PD- and 20 AD patients with early cognitive impairment) and 20 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 43 publications
5
46
0
6
Order By: Relevance
“…Significant increases in frontal delta power with decreases in beta and gamma power suggest an increased contribution of slow‐wave activity following drug administration. These findings are consistent with reports of underlying cortical dysfunction related to various neurological disorders and encephalopathies, regardless of the underlying etiology 25, 33, 34. As these changes were seen in both main and secondary analyses, they represent relative strong findings.…”
Section: Discussionsupporting
confidence: 91%
“…Significant increases in frontal delta power with decreases in beta and gamma power suggest an increased contribution of slow‐wave activity following drug administration. These findings are consistent with reports of underlying cortical dysfunction related to various neurological disorders and encephalopathies, regardless of the underlying etiology 25, 33, 34. As these changes were seen in both main and secondary analyses, they represent relative strong findings.…”
Section: Discussionsupporting
confidence: 91%
“…In these regions, the PD-D patients exhibited increased δ and θ power and decreased β power, which indicates slow EEG activity. When comparing AD patients, PD-D patients, PD patients without dementia, and controls, the highest δ and θ powers were observed in the PD-D patients and the lowest δ and θ powers were found in the controls (PD-D > AD > PD > CG) [22]. Similar patterns of highest δ energy and lowest α, β and γ energy in PD-D patients were observed in the current study.…”
Section: Discussionsupporting
confidence: 75%
“…In previous studies, it was found that temporal processing in PD appears to markedly affect beta and alpha rhythms in PD in motor cortex, although previous investigators did not focus on lower frequencies (Praamstra and Pope 2007). Recent work has implicated decreased theta in addition to alpha and beta frequencies in diagnosis of PD, in distinct brain regions (Benz et al 2014;Gu et al 2014Han et al 2013Praamstra and Pope 2007). Our work extends this line of research by focusing on MFC and linking spectral activity in PD patients with mechanistic theories (Cavanagh and Frank 2014) and single neuron activity that is consistently involved in temporal processing (Bekolay et al 2014;Kim et al 2013;Matell and Meck 2004;Narayanan and Laubach 2009;Niki and Watanabe 1979;Parker et al 2014;Xu et al 2014).…”
Section: Discussionmentioning
confidence: 99%